The Experiences of White Male Counsellors Who Work with First Nations Clients - Smith, D. Bruce; Morrissette, Patrick J. (Canadian Counselling and Psychotherapy Association, 2007)
This paper describes a qualitative study that investigated the experiences of White male counsellors who work with First Nations clients. Five experienced counsellors participated in individual, tape-recorded interviews, during which they described their experiences, yielding written protocols that were thematically analyzed. Results from this study revealed five predominant themes that included the following: (a) encountering difference, (b) establishing relationships, (c) a willingness to learn, (d) evolving professional identities, and (e) impact on self-awareness. Findings and implications for White counsellors and counsellor educators are included. Cet article décrit une étude qualitative examinant les expériences de conseillers masculins blancs travaillant avec des clients des Premières Nations. Cinq conseillers chevronnés ont participé à des entrevues individuelles enregistrées sur magnétophone, durant lesquelles ils ont décrit leurs expériences. Ces entrevues ont conduit à la rédaction de protocoles qui ont été analysés thématiquement. Les résultats de cette étude révèlent les cinq thèmes principaux suivants : (a) l'expérience de la différence, (b) l'établissement d'une relation, (c) une volonté d'apprendre, (d) l'évolution des identités professionnelles et (e) l'impact sur la conscience de soi. Il est fourni des conclusions et des implications à l'usage des conseillers blancs et des conseillers-éducateurs.